2019
DOI: 10.3390/su11154159
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Waste Logistics and the Development of Trade in Recyclable Raw Materials in Poland and Hungary

Abstract: This article aims to propose a methodological framework to determine the degree of the dynamic impact of the effect of activities in the field of sustainable waste logistics on the development of trade in recyclable raw materials in the chosen countries of the European Union, especially in Poland and Hungary. In order to determine the dynamic interdependence between the indicated phenomena, econometric tools associated with the vector autoregression model were used, namely: Granger causality tests, impulse res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
6
0
1
Order By: Relevance
“…However, as many studies was shown, that it can also be used to check the achievement of sustainable development goals [35] or prioritizing sustainable urban regeneration in sensitive areas [36], which points to its universality. Based on the literature data [8,9,15,37,38,39,40,41,42,43], the main factors for individual groups of the analysis were determined, i.e. strengths, weaknesses, opportunities, threats.…”
Section: Methodology Of Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as many studies was shown, that it can also be used to check the achievement of sustainable development goals [35] or prioritizing sustainable urban regeneration in sensitive areas [36], which points to its universality. Based on the literature data [8,9,15,37,38,39,40,41,42,43], the main factors for individual groups of the analysis were determined, i.e. strengths, weaknesses, opportunities, threats.…”
Section: Methodology Of Researchmentioning
confidence: 99%
“…Green transport is an element of green logistics and is defined as the management of supplies (materials and products) that reduces the environmental and energy footprint of the distributed goods. Green Transport involves an organization's activities that take environmental considerations into account and integrate it into supply chain management to change the environmental performance of suppliers and customers [9]. To address the significant contribution of transport (professional transport) to greenhouse gas emissions, the government continues to develop a green transport strategy (GTS).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors found that trade issues in recycled raw materials are not widely studied in the scientific literature. For example, in their article, Mesjasz-Lech and Michelberger (2019) propose a methodological framework for EU countries to determine the development impact of sustainable waste logistics TRRM. Liang et al (2021) researched the generation, trade, management, and processing of waste plastic in Asia (Liang et al 2021).…”
Section: Trade In Recyclable Raw Materialsmentioning
confidence: 99%
“…The listed tools establish causal links between CE-related private investments and an indicator defining the trade development in recycled raw materials. Adequately delayed values of the forecasted measures show how accurate the forecasts of recyclable trade volumes are (Mesjasz-Lech and Michelberger 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Эта концепция может быть поддержана обратной логистикой (управлением возвратов отходов населению). Поэтому учеными изучаются тенденции размеров потоков муниципальных отходов [34].…”
unclassified